ABILITY TO RESTORE REPRODUCTIVE SYSTEM IN PATHINTS WITH COMBINED FORM OF HYPERANDROGENISM - R. A. Saidova; O. A. Monastyrnaya; A. G. Davudova (Акушерство, гинекология и репродукция, 2016)
Combined form of hyperandrogenism is one of the leading pathogenic causes of menstrual and reproductive disfunctions. Anovulation state causes an increase in the level of the main androgens, and the luteal phase deficiency is a consequence of the negative impact of hyperandrogenism. Conducting individual pathogenesis-based therapy, taking into account the condition of the reproductive system, allows of ovulation and pregnancy on the background normalization of androgen metabolism and other indicators of the functioning of the reproductive system.